Bicuspid aortic valve fusion length correlates with maximum aortic diameter and heamodynamic abnormalities: a 4D flow CMR study. (13th July 2021) - Guala, A; Teixido-Tura, G; Dux-Santoy, L; Ruiz-Munoz, A; Valente, F; Galian, L; Gutierrez, L; Gonzalez-Alujas, T; Johnson, K; Wieben, O; Sao-Aviles, A; Ferreira-Gonzalez, I; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Guala A. received funding from the Spanish Ministry of Science, Innovation and Universities. Background: Bicuspid aortic valve (BAV), a congenital heart defect, is associated with ascending aorta dilation, possibly via alteration of aortic blood flow [1]. In BAV abnormal flow condition have been associated with aortic extracellular matrix dysregulation and elastic fiber degeneration [2]. Current morphological classification of BAV patients with aortic valve with a single fusion between two adjacent leaflets does not allow for risk stratification. Purpose: This research work tested whether the extent of fusion between leaflets is related to AAo diameter and flow alterations. Methods: Ninety BAV patients free from moderate and severe aortic valve disease and with no previous aortic or aortic valve surgery or replacement were prospectively enrolled. A comprehensive magnetic resonance protocol comprised a stack of double-oblique 2D balanced steady-state free-precession (bSSFP) cine CMR of the aortic valve, which was used to measure the length of the fusion between leaflets, a cine CMR at the level of the pulmonary bifurcation to assess aortic diameter and 4D flow MRI sequence to assess flow characteristics and regional stiffness [3]. Jet angle and flow radial displacement, quantifying the extent of flow eccentricity, and systolic flow reversal ratio (SFRR), assessing the relative amount of backward flow during systole, were computed at 8 equidistant planes in the ascending aorta and 4 equidistant planes in the aortic arch [4]. A two-tailed p-value < 0.05 was considered statistically significant. Results: The length of leaflet fusion varied widely (median 7.7 mm, inter-quartile range [5.5; 10.2]), Table 1). In bivariate analysis, fusion length was also associated to ascending aortic diameter (R = 0.391, p < 0.001), age (R = 0.313, p = 0.005) and body surface area (R = 0.396, p < 0.001). It was also positively related to flow abnormalities: like displacement in the proximal and distal ascending aorta, jet angle in the mid ascending aorta, and SFRR in the ascending aorta and the aortic arch (see Figure 1). The association between fusion length and ascending aorta diameter persisted in multivariate analysis after correction for age (p = 0.006). Conclusions: Bicuspid aortic valve fusion extent varies greatly and it is associated with aortic diameter, possibly through flow alterations. Prospective longitudinal studies are needed to establish whether fusion length may allow for risk stratification in bicuspid aortic valve patients.